An Approach of Vulnerability Testing for Third-Party Component Based on Condition and Parameter Mutation - Jinfu Chen; Jiamei Chen; Yongzhao Zhan; Weihe Chen; Rubing Huang (The Scientific World Journal)
The research on component vulnerability testing is critical. In this paper, an approach of vulnerability testing is proposed based on condition mutation and parameter mutation in order to effectively detect the explicit vulnerabilities of third-party components. To start with, the Pre-condition Mutation Algorithm (PCMA) is presented to generate mutants set of the pre-condition and test cases are generated based on these mutants. Then, the Single Parameter Mutated Values (SPMV) procedure is addressed to generate parameter values based on mutation operators of parameter specification. These values are then taken as the input of the Test Case Generation Algorithm based on the Parameter Constraint (TCGPC), which is addressed to generate test case set violating the parameter constraint. The explicit vulnerabilities can be detected by the vulnerability detecting algorithm based on the test cases of condition and parameter mutation. The experiments show that our approach can detect explicit vulnerability faults of third-party components. Furthermore, the proposed approach can detect more vulnerability faults than other related approaches such as condition coverage methods, fuzzy testing method and boundary value method.